Morphometric assessment of periodontal tissues in relation to periodontal disease in dogs - Kyllar, Michal; Doskarova, Barbora; Paral, Vaclav (Journal of veterinary dentistry, 2013)
Dimensions of periodontal tissues are thought to predispose to the development of periodontal disease in man and dogs. Several studies have suggested that thin gingiva correlates with an increased incidence of periodontal disease. In this study, we hypothesized that the dimensions of periodontal tissues will vary in different breeds of dogs and could possibly correlate with the incidence of periodontal disease. Forty-two jaws of dogs aged up to 5-years were examined post-mortem and gingival and alveolar bone thickness were measured using methods of transgingival probing and digital calipers, respectively. Dogs were divided into three groups based on their body weight. Group I (< 5.0 kg; n=21), group II (5 to 10 kg; n=11), and group III (10 to 15 kg; n=10). Thickness of gingiva ranged from 0.30-mm to 3.2-mm and was relatively thinner in group I than in group II and III based on the means of ratios comparison. Alveolar bone thickness ranged from 0.27-mm to 4.1-mm and was relatively thinner in group I compared with groups II and III. Our study showed significantly thinner gingiva and alveolar bone in toy breed dogs compared with small and medium-sized breed dogs. Both gingival and alveolar bone dimensions may be predictors for severity of periodontal disease and influence clinical outcome in certain periodontal surgical procedures.
Keywords: předpověď; Animals; mandibula; Female; Cephalometry; Periodontics; Gingiva; ženské pohlaví; nemoci psů; gingiva; nemoci parodontu; Mandible; Dog Diseases; Dogs; Forecasting; parodont; kefalometrie; mrtvola; tělesná hmotnost; maxila; Male; Cadaver; processus alveolaris; Periodontium; Body Weight; Maxilla; Alveolar Process; zvířata; mužské pohlaví; parodontologie; Dental Arch; Periodontal Diseases; psi; zubní oblouk